Performing Suffering on TikTok: Digital Discourse, Self-Disclosure, and the Commodification of Mental Illness in Indonesia - Syafrida Nurrachmi Febriyanti (INJECT (Interdisciplinary Journal of Communication), 2025)
This article examines how Indonesian TikTok creators narrate bipolar disorder, depression, and anxiety, and how platform logics shape those representations. Using a corpus-driven Digital Discourse Analysis operationalized across four elements: Text, Interaction, Context, and Ideology/Power (Jones, 2012), we analyze four public accounts over January–July 2025. The corpus includes videos, captions, on-screen text, hashtags, and top-level comments, complemented by a brief review of Indonesia’s mental-health landscape to situate platform uptake. Findings show that self-disclosure works simultaneously as therapeutic expression and performative practice: creators signal authenticity while adapting to affordances/algorithms (FYP, hashtags, duet/stitch, trending sounds), with reach asymmetries mediating whose narratives circulate. Interactional practices, creator replies, comment curation/pinning, and audience boundary-policing, co-construct norms of “responsible telling.” Notably, counter-evidence indicates that supportive uptake can occur without trending sounds or heavy tagging when contextual fit is strong, suggesting algorithms are consequential but not exhaustive determinants. Contributions include bridging Hall’s representation with Jones’s Digital Discourse Analysis in a Global South setting and demonstrating how authenticity, intimacy, and visibility become forms of symbolic and platform value. Implications point to harm-minimization for creators (bounded disclosure, resource signposting), opportunities for public-health messaging that leverages peer-support affordances, and platform nudges (e.g., prompts to add help resources on mental-health tags) to preserve supportive communication without incentivizing the aestheticization of distress.